Producing animation - Winder, Catherine; Dowlatabadi, Zahra (Focal Press, 2011)
A comprehensive guide to the production industry. It covers the process from script to screen while defining the role of the producer at each phase. It features content such as sidebars on key topics from industry experts, discussions on CG, 2D and stereoscopic production processes, and an overview on marketing and distributing your project.